An adaptive transgenerational effect of warming but not of pesticide exposure determines how a pesticide and warming interact for antipredator behaviour. (February 2019) - Tran, Tam T.; Janssens, Lizanne; Dinh, Khuong V.; Stoks, Robby
Abstract: The impact of pesticides on organisms may strongly depend on temperature. While many species will be exposed to pesticides and warming both in the parental and offspring generations, transgenerational effects of pesticides under warming are still poorly studied, particularly for behaviour. We therefore studied the single and combined effects of exposure to the pesticide chlorpyrifos (CPF) and warming both within and across generations on antipredator behaviour of larvae of the vector mosquito Culex pipiens . Within each generation pesticide exposure and warming reduced the escape diving time, making the larvae more susceptible to predation. Pesticide exposure of the parents did not affect offspring antipredator behaviour. Yet, parental exposure to warming determined how warming and the pesticide interacted in the offspring generation. When parents were reared at 24 °C, warming no longer reduced offspring diving times in the solvent control, suggesting an adaptive transgenerational effect to prepare the offspring to better deal with a higher predation risk under warming. Related to this, the CPF-induced reduction in diving time was stronger at 20 °C than at 24 °C, except in the offspring whose parents had been exposed to 24 °C. This dependency of the widespread interaction between warming and pesticide exposure on an adaptive transgenerational effect of warming is an important finding at the interface of global change ecology and ecotoxicology. Graphical abstract: Highlights: We studied transgenerational effects of pesticide and warming on mosquito behaviour. Exposure to chlorpyrifos (CPF) and warming reduced antipredator behaviour. The effect of CPF on antipredator behaviour was smaller under warming. Parental exposure to warming shaped combined effect of CPF and warming in offspring. Abstract : An adaptive transgenerational effect of exposure to warming, but not to a pesticide determines how pesticide and warming interact for antipredator behaviour in the offspring.